2017
DOI: 10.1186/s12875-016-0574-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and physicians’ perceptions and attitudes about oral anticoagulation and atrial fibrillation: a qualitative systematic review

Abstract: BackgroundOral anticoagulant therapy reduces the risk of stroke in patients with atrial fibrillation, but many patients are still not prescribed this therapy. The causes of underuse of vitamin K antagonists oral anticoagulants are not clear but could be related, in part, to patients’ and physicians’ perceptions and attitudes towards the benefits and downsides of this treatment. The purpose of this systematic review was to evaluate and synthesize patients’ and physicians’ perceptions and attitudes towards the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 42 publications
7
68
0
Order By: Relevance
“…Frequent testing is unavoidable in ensuring safe anticoagulation; however, the provision and setup of testing centres can be addressed. Similar issues have been raised in research elsewhere [24,25]. Capillary testing is a quick and easily applicable alternative to venous sampling.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Frequent testing is unavoidable in ensuring safe anticoagulation; however, the provision and setup of testing centres can be addressed. Similar issues have been raised in research elsewhere [24,25]. Capillary testing is a quick and easily applicable alternative to venous sampling.…”
Section: Discussionmentioning
confidence: 67%
“…To ensure optimal adherence to DOACs in patients prescribed additional medicines, perhaps efforts should be directed towards addressing adherence in the context of an entire regime rather than a single drug. This does not negate addressing knowledge deficits or patient beliefs surrounding their illness and anticoagulation in the consultation as this can be vital in ensuring good adherence [25,37]. Furthermore, research demonstrates AF patients value these discussions when considering anticoagulation [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent qualitative systematic review postulated the lack of patient information as one of the most important reasons for vitamin K antagonists underuse. 41 Although Dantas et al 37 demonstrated that only minimal knowledge of patients is needed to allow acceptance of OAC, doctors should seek shared decisions. This is even more important, when evidence for drug treatment is marginal, 42 which is definitely not the case in patients with high risk scores for AF.…”
Section: Discussionmentioning
confidence: 99%
“…Underestimation by clinicians of the benefits of anticoagulant therapy for stroke prevention in atrial fibrillation coupled with an overestimation of bleeding risk is known to be a factor in the under-use of this highly effective treatment. 25,26 It is no surprise that most GPs did not know the correct answers. The authors would not expect any individual to remember a high volume of precise figures.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%